Nir-Konflik dalam Keluarga: Studi Analisis Perspektif Kearifan Lokal dan Islam - Muhammad Asyari (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT This Peper will describe how family violence (the smallest institution in society) disturbs and impedes daily activities in family life. This conflict can have an impact ranging from small scales such as separation of beds to even minor violence to the greatest impact of divorce and hostility between families of both sides. Departing from that, minimizing up to shifting the potential for conflict in a positive way seems to be necessary. One of the worthy re-glances of local wisdom (local wisdom), local wisdom is the values that live in society and followed by its members, and local wisdom is actually a development of the teachings of revelation or old values that have experienced Islamization. The practice of local wisdom and the teachings of Islam as the basis of conflict resolution have been practiced in the history of Islamic civilization. By minimizing the conflict from the family, it is expected to suppress the potential for greater conflict let alone threaten the security of nation and state. Keywords: Nonviolence, Family, Local Wisdom and Islamic Teachings